NEGOTIN LOWLAND IRRIGATION SYSTEM UPGRADING - Popović, Vesna; Kljajić, Nataša; Subić, Jonel (Economics of Agriculture, 2014)
According to FAO concept of irrigation modernisation, to be effective, an irrigation system must be based on improved irrigation effciency, reduced operation and maintenance costs and improved cost recovery based on raised agricultural productivity, with due consideration to the institutional and legal-related issues and environment protection. To make the irrigation system successfully upgraded, the project needs to undergo a comprehensive analysis of the factors that lead to the modernization. Using the IPTRID/FAO-AGLW methodological approach of addressing causes for irrigation modernization, the authors in the paper review technical, socio-institutional, economic-fnancial and environmental causes for upgrading of the irrigation system in the Negotin lowland and give some recommendations for successful realization of this project, based on international and regional experiences and adjusted to specifcities of local agriculture and rural communities.